Short Term Outcome of Acute ST Elevation Myocardial Infarction in a Tertiary Care Cardiac Center - Shrestha, Hemant; Gajurel, Ratna M; Poudel, Chandra M; Thapa, Sanjeev; Sayami, Arun (Journal of Institute of Medicine Nepal, 2020)
Introduction Acute ST Elevation Myocardial infarction (STEMI) is a cardiovascular emergency and is associated with significant adverse short and long-term outcome. The objective of this study was to determine the short-term outcome in terms of heart failure, myocardial reinfarction, stroke, hospital readmission and mortality in patients admitted with STEMIMethodsIt was a prospective observational study conducted at Manmohan Cardiothoracic Vascular and Transplant Center, Kathmandu from May 2014 to April 2015. All patients admitted with diagnosis of STEMI during study period were enrolled. Patients were treated on the basis of existing guidelines. Mode of management, adverse outcomes and mortality of patients during the study period were evaluated. The discharged patients were followed up for 30 days. Statistical analysis was performed with SPSS version 20. Ethical approval was taken from the Institutional Review Committee of Institute of Medicine.ResultsThe median duration of presentation was 20 hours, and only 40% of the patients presented within 12 hours of symptom onset. Primary PCI was performed in 50 (33%), thrombolysis was performed in 29(19%) and conservative medical management was done in 72 (48%) patients. Overall outcome occurred in 52 (37.7%) patients. In hospital and 30 day mortality was 14 (9.2%) and 17 (11%) respectively. Heart failure was present in 28(18.5%), myocardial reinfarction 8 (5%), stroke 4 (2.6%), and hospital readmission was 18 (12%). Conservatively treated patients had significantly more adverse outcomes (p=0.02). More patients in conservatively managed group had hospital readmission. (p=0.04)ConclusionThere were more overall adverse outcomes in conservatitley managed group which is mainly due to more hospital readmission.